2007
DOI: 10.1158/1535-7163.mct-07-0336
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of NF-κB by 3,3′-diindolylmethane contributes to increased apoptosis induced by chemotherapeutic agent in breast cancer cells

Abstract: Constitutive activation of Akt or nuclear factor-KB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 49 publications
5
87
0
Order By: Relevance
“…Cyclin D1 and cMyc, two NF-B target genes have an important role in cell growth and proliferation (73,74), and key angiogenesis factors such as vascular endothelial growth factor (VEGF) and interleukin-8 (64), are directly or indirectly enhanced by NF-B activation. Cancer growth inhibition via NF-B inhibition has been shown in colon (75), and the similar results has been shown in other several flavors of human neoplasia such as lung (76) and breast (77). To investigate the role of NF-B in inflammation-induced tumor growth, one study of experimental murine colon cancer metastasis model revealed Volume 6 Number 5 October 2009 that lipopolysaccharide (LPS)-induced metastatic growth response depends on both TNF- production by host hematopoietic cells and NF-B activation in tumor cells.…”
Section: The Role Of Nf-b In Promoting Carcinogenesis Of Colorectalsupporting
confidence: 71%
“…Cyclin D1 and cMyc, two NF-B target genes have an important role in cell growth and proliferation (73,74), and key angiogenesis factors such as vascular endothelial growth factor (VEGF) and interleukin-8 (64), are directly or indirectly enhanced by NF-B activation. Cancer growth inhibition via NF-B inhibition has been shown in colon (75), and the similar results has been shown in other several flavors of human neoplasia such as lung (76) and breast (77). To investigate the role of NF-B in inflammation-induced tumor growth, one study of experimental murine colon cancer metastasis model revealed Volume 6 Number 5 October 2009 that lipopolysaccharide (LPS)-induced metastatic growth response depends on both TNF- production by host hematopoietic cells and NF-B activation in tumor cells.…”
Section: The Role Of Nf-b In Promoting Carcinogenesis Of Colorectalsupporting
confidence: 71%
“…LNCaP and C4-2B prostate cancer cells were seeded in 96-well plates. After 24 h, the cells were treated with 10, 30, and 40 Amol/L DIM followed by treatment of Taxotere with 0.5, 1.0, and 1.5 nmol/L for 24 to 72 h. After treatment, the cell growth studies were done by MTT as described earlier (26,27).…”
Section: Methodsmentioning
confidence: 99%
“…The cytoplasmic histone/DNA fragments from prostate cancer cells treated with 10 or 30 Amol/L DIM followed by treatment of Taxotere with 1.0 or 1.5 nmol/L for 24, 48, or 72 h were extracted and the Cell Death Detection ELISA Kit (Roche) was used to detect apoptosis in prostate cancer cells as described earlier (11,26,27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations